Climate variability and trends in the Valkea-Kotinen region, southern Finland: comparisons between the past, current and projected climates - Jylhä, Kirsti; Laapas, Mikko; Ruosteenoja, Kimmo; Arvola, Lauri; Drebs, Achim; Kersalo, Juha; Saku, Seppo; Gregow, Hilppa; Hannula, Henna-Reetta; Pirinen, Pentti
2015